2021
DOI: 10.1001/jamanetworkopen.2021.21403
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Cost-effectiveness of Endoscopic Screening for Upper Gastrointestinal Tract Cancer in High-Risk Areas in China

Abstract: IMPORTANCE Upper gastrointestinal tract cancer, including esophageal and gastric cancers, in China accounts for 50% of the global burden. Endoscopic screening may be associated with a decreased incidence of and mortality from upper gastrointestinal tract cancer.OBJECTIVE To evaluate the cost-effectiveness of endoscopic screening for esophageal and gastric cancers among people aged 40 to 69 years in areas of China where the risk of these cancers is high. DESIGN, SETTING, AND PARTICIPANTSFor this economic evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…A useful output when using DCEs was how the probability of choosing a given option changes with attribute levels ( 37 ). We found that the 47.46% participation rate of current screening strategies was very close to the actual uptake rates of 48.62% and 49% ( 7 , 10 ), indicating that the predicted results in this study were accurate and dependable. We also found that the UGC screening strategies with follow-up, shorter interval, less pain, higher mortality reduction, and lower costs had a higher participation rate.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A useful output when using DCEs was how the probability of choosing a given option changes with attribute levels ( 37 ). We found that the 47.46% participation rate of current screening strategies was very close to the actual uptake rates of 48.62% and 49% ( 7 , 10 ), indicating that the predicted results in this study were accurate and dependable. We also found that the UGC screening strategies with follow-up, shorter interval, less pain, higher mortality reduction, and lower costs had a higher participation rate.…”
Section: Discussionsupporting
confidence: 66%
“…Xia et al. ( 10 ) noted that an endoscopic screening for EC and GC would be more cost-effective than no screening regardless of the initial screening age or screening interval. This finding is consistent with the conclusion reported in our previous research, and the selected attributes and levels in this study draw on the dominance strategies screened from our previous work.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study based on a calibrated microsimulation model to comprehensively evaluate the long-term clinical and economic consequences of GC screening strategies. The previous studies mainly evaluated the cost-effectiveness of endoscopic screening programs directly for GC high-risk populations ( 45 , 46 ). Actually, most of the high GC risk areas in China are rural, with scarce medical resources or limited endoscopic screening facilities ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gastroscopy is widely used to diagnose or treat esophageal and gastric diseases and may reduce the incidence and mortality rates of upper gastrointestinal tract cancer in areas with high cancer risk in China ( Xia et al, 2021 ). In 2018, 22.2 million gastrointestinal endoscopies were performed in the United States, and 284,844 new cases of gastrointestinal cancer were diagnosed ( Peery et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%